Analysis of students' critical thinking skills in solving mathematics problems in terms of students' initial ability - Harahap, Adek Nilasari; Bentri, Alwen; Musdi, Edwin; Yerizon, Yerizon; Armiati, Armiati (Indonesian Journal of Science and Mathematics Education, 2024)
This study aimed to analyze the effect of initial mathematics ability on the critical thinking ability of seventh-grade students of SMP Negeri 8 Padangsidimpuan in solving mathematics problems. Using a qualitative descriptive method, this study involved six students from class VII-D who were selected based on the initial ability test, which was categorized into high, medium, and low. The analysis focuses on four aspects of critical thinking: interpretation, analysis, evaluation, and inference. Based on the data obtained through critical thinking tests and interviews, the results showed significant variations in critical thinking ability according to students' initial ability levels. Students with high initial ability showed full mastery of all four critical thinking indicators, while students with moderate ability achieved two indicators, and students with low initial ability did not fulfil the critical thinking indicators. These results indicate that initial math ability significantly affects student's critical thinking skills in the context of mathematical problem-solving. The implications of this study provide important insights for developing educational strategies that target improving critical thinking skills, taking into account students' initial mathematical abilities.